1979
DOI: 10.3109/10826087909041901
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Three- Versus a Five-Week Alcohol Treatment Program

Abstract: Eighty-six male alcoholic inpatients were randomly assigned to comparable 3- or 5-week treatment progrrams. Psychometric testing at the beginning and the end of treatment was supplemented by follow-up data 6 months after discharge. While both the 3- and 5-week groups demonstrated significant improvement on both MMPI and follow-up data, few differences between the groups were revealed. The comparable results obtained offer little justification for prolonging inpatient treatment beyond 3 weeks. It is suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…When accompanied by outpatient aftercare therapy, it appears that length of hospitalization may be shortened for many patients without appreciably reducing treatment efficacy. This finding is consistent with several other studies involving random assignment (Mosher et al, 1975;Page & Schaub, 1979;Stein et al, 1975;Willems et al, 1973). In addition, significantly more subjects assigned to the 7week program dropped out of inpatient treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When accompanied by outpatient aftercare therapy, it appears that length of hospitalization may be shortened for many patients without appreciably reducing treatment efficacy. This finding is consistent with several other studies involving random assignment (Mosher et al, 1975;Page & Schaub, 1979;Stein et al, 1975;Willems et al, 1973). In addition, significantly more subjects assigned to the 7week program dropped out of inpatient treatment.…”
Section: Discussionsupporting
confidence: 91%
“…A number of randomized experimental studies have generally found no differences at outcome associated with length of stay (Mosher, Davis, Mulligan, & Iber, 1975;Page & Schaub, 1979;Stein, Newton, & Bowman, 1975). After their treatment program was administratively shortened from 84 days to 60 days, Kish, Ellsworth, and Woody (1980) found that at 6-month follow-up a higher percentage of patients in the shorter program reported drinking since discharge.…”
mentioning
confidence: 99%
“…Page & Schaub [19] reported another study that examined the impact of longer intervention. They randomly assigned 86 alcoholics to either a 5-week or a 3-week in-patient programme.…”
Section: In-patient Versus Day Patient Interventionmentioning
confidence: 99%
“…In some cases, a longer LOS is promoted as a significant factor in maintaining abstinence, 13 with an increased likelihood of abstinence in addition to other functional outcomes including less legal involvement, employment increases, and improvement in comorbid disorders. 22 Other research has determined that LOS does not influence the maintenance of abstinence, 23 while longer term follow-ups indicate that the difference in abstinence rates due to LOS dissipates over time. 12 There is also evidence to support the hypothesis that LOS may differentially impact abstinence versus engagement in other recovery activities, with increased abstinence rates yet no difference on other outcomes, including overall functioning post-treatment.…”
Section: Adolescent Treatment Outcomes 367mentioning
confidence: 98%